PENGARUH KUALITAS PRODUK, HARGA DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA LIPAT PADA MASA PANDEMIC COVID-19: (Studi Kasus Pada Pengguna Sepeda Lipat Di Cilacap) - Esih Jayanti; Tarihoran, Anisa Herani (JURNAL EKONOMI, 2022)
Cycling is one of the choices of activity for some people during the Covid-19 pandemic and the adaptation period for new habits. Public enthusiasm for bicycles made by local businesses is also quite high. In line with the above, consumer decisions in purchasing folding bicycles can be influenced by marketing stimuli such as product quality, high prices with good quality assurance and the uniqueness of the product design. This study aims to examine and analyze the effect of product quality, price and product design on purchasing decisions. Data was collected by distributing questionnaires to 58 consumers or folding bicycle users in Cilacap. Analysis of the data in this study using the help of statistical software data processing results. The sampling technique used is the census method and the data testing technique used in this study includes validity test with factor analysis, reliability test, Succesive Interval (MSI) Method, classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis. The results of the partial test (t test) show that quality has a significant effect on purchasing decisions, price and product design have no significant effect. Simultaneous test results (Test F) show that product quality, price and product design simultaneously have a significant positive effect. The results of the coefficient of determination test indicate that product quality, price and product design provide sufficient contribution to purchasing decisions